G278 Pilot of opportunistic seasonal influenza vaccination for children attending the paediatric emergency department. (24th May 2017) - Isba, R; Cleland, J; Cooke, D; Lees, A; Higgins, S; Hilditch, K
Abstract : Aims: Seasonal influenza remains a major cause of mortality and morbidity worldwide. As well as groups of highly-susceptible individuals (e.g. those with an underlying medical condition), there are also so-called 'super-spreaders'. These individuals – for example pre-school children – are able to easily and widely transmit the virus. In England, annual seasonal influenza vaccination is offered to high-risk individuals and, in the 2014/15 season, all 2, 3, and 4 year olds were added to the programme. Despite the introduction of an intranasal vaccination, coverage among preschool children remained low in 2015/16, with only 30%– 40% uptake. A small body of evidence exists to suggest that opportunistic vaccination in the Paediatric Emergency Department (PED) is possible. Many of the hurdles to opportunistic routine childhood vaccination, e.g. parental recall of vaccination status, do not apply to seasonal influenza vaccination. The PED may therefore offer an opportunity to immunise children, particularly those in hard-to-reach groups who may preferentially access secondary care. The overall aim of this work was to deliver a pilot programme of opportunistic seasonal influenza vaccination, via a PED, to all patients (and accompanying household members) aged 2, 3, or 4 years old, and older at risk children. Methods The pilot ran 9am – 5 pm, Monday to Friday, October to December, in a single PED. All staff identified participants and a small number of senior nurses were trained in-house to deliver the vaccine. National consent paperwork was adapted for the acute care setting in collaboration with clinicians and commissioners. Results: In the first half of the pilot, 40 eligible children were vaccinated, a small number declined the vaccine, and there were no adverse events reported. Children aged 2–4 accounted for more than 90% of those vaccinated. A large number of children were ineligible on their day of attendance, with fever or wheeze the most common contraindications. Many parents/carers were not aware of the national programme and their child's eligibility. Conclusion: It is possible to offer seasonal influenza vaccination in the PED. A full evaluation of the programme is planned which will offer a framework for those hoping to adopt and locally adapt this approach next season.